Effect of complement component 5 polymorphisms on mastitis resistance in Egyptian buffalo and cattle. (August 2018) - El-Halawany, Nermin; Shawky, Abd-El-Monsif A.; Al-Tohamy, Ahmed F.M.; Abdel-Latif, Magdy A.; Abdel-Shafy, Hamdy; Ghazi, Yasser A.; Neuhoff, Christiane; Schellander, Karl
Abstract: Mastitis is one of the costliest diseases affecting the world's dairy industry. The important contribution of complement Component 5 (C5) to phagocytosis, which plays a major role in the defence of the bovine mammary gland against infection, makes this component of innate immunity a potential contributor in defending udder against mastitis. The objectives of this study were to sequence and analyse the whole coding region of the C5 gene in Egyptian buffalo and cattle, to detect any nucleotide variations (polymorphisms) and to investigate their associations with milk somatic cell score (SCS) as an indicator of mastitis in dairy animals. We sequenced a buffalo C5 cDNA fragment of 5336 bp (KP221293) and a cattle C5 cDNA fragment of 5303 bp (KP221294), which included the whole coding region and 3-UTR. Buffalo and cattle C5 cDNA shared sequence identity of 99%. The predicted complement C5 proteins consist of 1677 amino acid residues in both animals, one amino acid less than in humans and three amino acids more than in mouse C5 protein. Comparing cDNA sequences of different animals revealed nine novel SNPs in buffalo and seven SNPs in cattle, with two of them being novel. The association analysis revealed that five SNPs in buffalo are highly associated with SCS; indicating the contribution of complement C5 variants in buffalo mastitis resistance. No significant associations were detected between C5 variants and SCS in cattle. This is the first report about C5 variants in buffalo and its association with SCS. Highlights: Buffalo and cattle C5 mRNA were sequenced and characterized for first time. Nine novel SNPs in buffalo C5 and seven SNPs in cattle C5 were detected. Five SNPs in buffalo C5 are significantly associated with SCS. This is the first association analysis of C5 variants with milk SCS in buffalo and cattle.